DETERMINANTS OF CASH HOLDINGS OF CONSUMER NON-CYCLICALS FIRM LISTED IN INDONESIA STOCK EXCHANGE - Ariel, Clayden; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2024)
Cash is one of the most important asset owned by a firm. Cash functions to finance all firm’s operating activities. Without cash firm’s operational activities can’t run smoothly. Firms hold a certain amount of cash, this is called cash holdings. The level of cash holdings owned by a firm surely need to be managed well. This research aimed to empirically prove the effect of financial leverage, profitability, capital expenditure, firm size, and growth opportunity on cash holdings. The populations used in this research was 105 consumer non-cyclicals firms that was listed on Indonesia Stock Exchange (IDX) during the 2020-2022 period. The sampling method used was the purposive sampling method. The sample used in this research was 50 consumer non-cyclicals firms that was listed in IDX during the 2020-2022 period. The data used for this research was secondary data. The hyphothesis testing method used was multiple linear regression method. The statistical tool used for data processing in this research was Eviews version 12.0. The model that was most suited for this research was the Random Effect Model (REM). The results of this research showed that financial leverage, capital expenditure, and growth opportunity had a negative effect on cash holdings, profitability had a positive effect on cash holdings, while firm size didn’t have any effect on cash holdings. The results of this research implied that managers and investors should consider the level of financial leverage, profitability, and capital expenditure in assesing cash holdings to make a decision.